Analysis of Mechanical Durability, Hydrophobicity, Pyrolysis and Combustion Properties of Solid Biofuel Pellets Made from Mildly Torrefied Biomass - Kanageswari Singara veloo; Anthony Lau; Shahab Sokhansanj (Energies, 2025)
The production of solid biofuels from torrefied biomass holds significant potential for renewable energy applications. Durable pellet formation from severely torrefied biomass is hindered by the loss of natural binding properties, yet studies on mild torrefaction that preserves sufficient binding capacity for pellet production without external binders or changes to die conditions remain scarce. This paper investigated the production of fuel pellets from torrefied biomass without using external binders or adjusting pelletization parameters. Experiments were conducted using a mild torrefaction temperature (230 °C and 250 °C) and shorter residence time (10, 15, and 30 min). The torrefied materials were then subjected to pelletization using a single-pellet press; and the influence of torrefaction on the mechanical durability, hydrophobicity, and fuel characteristics of the pellets was examined. Results indicated that the mass loss ranging from 10 to 20% among the mild torrefaction treatments was less than the typical extent of mass loss due to severe torrefaction. Pellets made from torrefied biomass (torrefied pellets) had improvement in the hydrophobicity (moisture resistance) when compared to pellets made from untreated biomass (untreated pellets). Improved hydrophobicity is important for storage and transportation of pellets that are exposed to humid environmental conditions, as it reduces the risk of pellet degradation and spoilage. Thermogravimetric analysis of the pyrolysis and combustion behaviour of torrefied pellets indicated the improvement of fuel characteristics in terms of a much higher comprehensive pyrolysis index and greater thermal stability compared to untreated pellets, as evidenced by the prolonged burnout time and reduced combustion characteristics index. Residence time had a more significant impact on pellet durability than temperature, but the durability of the torrefied pellets was lower than that of the untreated pellets. Further research is required to explore the feasibility of producing binder-free durable pellets under mild torrefaction conditions. Overall, the study demonstrated that mild torrefaction could enhance the fuel quality and moisture resistance of biomass pellets, offering promising advantages for energy applications, despite some trade-offs in mechanical durability.